Effects of Glutamate and Na+ on the Development and Enzyme Activity of the Oriental Migratory Locust, Locusta migratoria manilensis (Meyen) in Successive Generations - Xia ZHAO; Miao JIA; Lei WANG; Guang-chun CAO; Ze-hua ZHANG (Journal of Integrative Agriculture, 2014)
Rapid and mass rearing of Locusta migratoria manilensis is an urgent need to meet the increasing demand for food of people. In this study, the effects of four artificial feeds on the development, reproduction and the activities of detoxification and protective enzymes of L. migratoria manilensis in three successive generations were investigated. The results showed that sucrose and monosodium glutamate (MSG) significantly increased the net reproductive rate (R0) and the intrinsic growth rate (rm) of L. migratoria manilensis, but sodium chloride (0.17%) suppressed this increase. Furthermore, the artificial feed with sucrose and monosodium glutamate increased the activities of esterase (EST), acetylcholinesterase (AChE), glutathione-S-transferase (GST), multi-function oxidase (MFO), phenol oxidase (PO), catalase (CAT) and peroxidase (POD), but inhibited the activity of superoxide dismutase (SOD). However, sodium chloride (0.17%) increased the activities of EST, AChE, CAT and SOD, and inhibited the activities of MFO, GST, PO and POD. Correlation analysis found that the increasing of PO activity and the decreasing of SOD activities were significantly related with the increasing of the intrinsic growth rate (rm). The above results indicated that sucrose and monosodium glutamate could promote the development and reproduction of L. migratoria manilensis, but Na+ inhibit such promotion with the concentration above 0.2%. The activities of PO and SOD can be used as biochemical standard to assess the effect of artificial feed.